Half-plane partial slip contact problems with a constant normal load subject to a shear force and differential bulk tension. (September 2018) - Moore, M.R.; Ramesh, R.; Hills, D.A.; Barber, J.R.
Abstract: This article provides a new form of solution to half-plane contact problems in partial slip where a normal load has been applied, held constant and is subsequently loaded with both a shear force and differential bulk tension. It uses a formulation where a displacement correction is made to the fully stuck solution. An approximate solution is used to study an isolated contact edge, which employs an asymptotic solution to each edge of the contact. A comparison of the approximation with the exact solution is given to show the range of loading where the asymptotic solution gives good results.